Socialization of Safety Factors for Passengers of Traditional Ship Crossing Transport at Muara Angke Port Jakarta - Susanto, Primadi Candra; Thamrin, Thamrin; Yasin, Robiha; Ricardianto, Prasadja; Pahala, Yosi; Chairudin, Irwan (Asian Journal of Community Services, 2024)
The orderliness of service and operation of facilities and infrastructure is relatively low, and many factors contribute to it, such as the weak awareness of ship owners and companies in implementing an effective and implementable safety system in the field, the seaworthiness of ships that are more oriented towards certification which in fact is not supported by careful inspection, as well as supervision carried out by the government on the implementation (drilling) of shipping safety requirements is inconsistent.  The purpose of socialization to passengers who use traditional wooden ships is "Socialization of Safety Factors for Passengers of Traditional Ship Crossing Transport at Muara Angke Port Jakarta" the purpose of socialization is to prevent opportunities for violations in shipping not using Ring Life Buoys, Life Jackets and unethical behavior of ships passengers.